An innovation of power bank as a gift or souvenir for government or corporate agencies - Intan Nurshafiqah Binti Ismady (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The final year project is about designing and innovating of power bank as a gift or souvenir for government or corporate agencies. Power bank is universal, portable and a rechargeable power source designed for mobile phones and other rechargeable electronic devices. The desgning of power bank as a gift or souvenir has not widely develoed and prioritized in the market. The problem of the current power bank as souvenir products is not accomplishing of social needs. Besides that, some power bank in the market also having a problem on the capacity of battery. power banks with a lower capacity are the least preferred by consumers as they do not meet the higher requirement.